2019
DOI: 10.14202/vetworld.2019.2007-2016
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of the exposure to Toxoplasma gondii among horses in Algeria and analysis of risk factors

Abstract: Aim: The aim of this study was to assess the seroprevalence of the Toxoplasma gondii in horses in different parts of Algeria and to determine risk factors for the infection. Materials and Methods: A total of 736 blood samples were collected from horses of various breeds, gender, coat colors, and ages. All horses came from various farms, racecourses, and equestrian centers. The seroprevalence was investigated by three different methods: Indirect fluorescent antibody test (IFAT) as reference method, enzyme-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
0
1
Order By: Relevance
“…By contrast, other research revealed a negative relationship between age and T. gondii infection in horses as well as a high prevalence rate in younger horses, the latter of which may be mostly due to underdeveloped immune systems [ 39 ] or as a result of trans-placental transmission and horizontal infection of T. gondii resulting from the consumption of oocyst-contaminated food or water. In addition, recent research from other nations, in contrast to our findings, revealed no appreciable variation in the seroprevalence of T. gondii in horses from Mexico, southern Spain, Korea, and southern Italy within age classes [ 23 , 77 , 78 , 79 , 80 ].…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, other research revealed a negative relationship between age and T. gondii infection in horses as well as a high prevalence rate in younger horses, the latter of which may be mostly due to underdeveloped immune systems [ 39 ] or as a result of trans-placental transmission and horizontal infection of T. gondii resulting from the consumption of oocyst-contaminated food or water. In addition, recent research from other nations, in contrast to our findings, revealed no appreciable variation in the seroprevalence of T. gondii in horses from Mexico, southern Spain, Korea, and southern Italy within age classes [ 23 , 77 , 78 , 79 , 80 ].…”
Section: Discussioncontrasting
confidence: 99%